Informing creation of the FEEDS Toolkit to support parent-delivered interventions for eating, drinking and swallowing difficulties in young children with neurodisability: intervention use by neurodevelopmental diagnosis and healthcare professional role - Lindsay Pennington; Jill Cadwgan; Helen Taylor; Jeremy Parr; Christopher Morris; Morag Andrew; Diane Sellers; Deborah Garland; Emogene Shaw (BMJ Publishing Group, 2024)
Background The FEEDS (Focus on Early Eating, Drinking and Swallowing) study focused on interventions used to improve feeding for children with neurodisability and eating, drinking and swallowing difficulties (EDSD), and the outcomes viewed as important by healthcare professionals (HPs) and parent carers. The FEEDS Toolkit was created subsequently as an intervention decision aid to be used collaboratively by parent carers and HPs. This study aimed to inform on current intervention practices and influence toolkit design by ascertaining whether specific intervention use varied by a child's main diagnosis and by specific HP role.Methods FEEDS survey data were grouped by child's main diagnosis and HP role. Main diagnoses included autism spectrum disorder (ASD) n=183; Down syndrome (DS) n=69; cerebral palsy (CP) n=30). HPs included were speech and language therapists (SLT) n=131; occupational therapists (OT) n=63; physiotherapists (PT) n=57; paediatricians n=50; dieticians n=40; nurses n=32 and health visitors n=14.Results Most interventions were used commonly across diagnoses. However, some interventions were used more commonly with specific conditions, for example, positioning (CP 85%, DS 70%, ASD 23%, strategies/programmes aimed at changing behaviour at mealtimes (ASD 52%, CP 8%, DS 11%); visual supports (ASD 58%, CP 0%, DS 21%). HPs reported using a broad range of interventions, SLTs (mean=13.9), dieticians (12.3), OTs (12.7) and paediatricians (11.1). There was overlap between intervention use and HP role, for example, positioning (100% PT, 97% SLT, 94% OT, 73% paediatricians and 69% nurses).Conclusions Interdisciplinary working is common when managing EDSD, with all HP types using multiple interventions. A child's main diagnosis does not substantially influence intervention use, and the individual context of each child requires consideration in intervention selection. Study findings have supported development of the FEEDS Toolkit for use in feeding services.